Síndrome mononucleósico severo con hepatitis colestásica en un paciente inmunocompetente : presentación de un caso (2010)
ABSTRACT: Mononucleosis syndrome is frequently associated with the Epstein Barr virus (EBV), which is related with Burkitt lymphoma, non-differentiated nose-throat carcinoma and lympho-proliferative illness. There is a serology association between the infection and Hodgkin’s disease and, in addition, the pathogenesis of the uterus neck cancer and EBV relation is studied. The reported clinic case patient presented a meaningful increase in reactive lymphocytes with abnormal morphological characteristics and important clinical complications such as multiple adenopathies, hepatomegaly, splenomegaly, hypertransaminases and hyperbilirubinemia, which excluded various differential diagnoses. Finally, according to the clinical history, the diagnostic results and the evolution of the patient, it is concluded that the diagnosis is a mononucleosis syndrome in a patient without immune deficiency and with cholestasic hepatitis due to an infection with EBV. The immunohistochemical studies of the ganglion biopsy allowed the exclusion of a diagnosis of lymphoma; consequently, the activated cells are not neoplastic.